Trace Element Supplementation In Palm Oil Mill Effluent (Pome) Anaerobic Digestion System For Methane Yield Enhancement - Choong, Yee Yaw (2019)
Palm oil mill effluent (POME) is an organic waste which can be converted into biogas (methane) as renewable energy by anaerobic digestion. Among the strategies for improving the methane yield of POME, the aspect of trace element has been neglected. From the literatures, iron (Fe), nickel (Ni) and cobalt (Co) are the most demanded elements for the anaerobic digestion system as micronutrient. Not forgetting, the element bioavailability must be considered, as it is more representative which reflects the available amount of element for interacting with the biological systems.